2021
DOI: 10.3389/fonc.2021.646211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pelvic Bone Marrow Sparing Intensity Modulated Radiation Therapy on Acute Hematologic Toxicity in Rectal Cancer Patients Undergoing Chemo-Radiotherapy

Abstract: BackgroundWhile chemo-radiotherapy improves local control in patients with locally advanced rectal cancer, it can also increase acute hematological toxicity (HT), which leads to poor outcomes. Patients receiving bone marrow radiation have been shown to develop acute HT. However, the safety and efficacy of bone marrow sparing is undetermined. The aim of our study was to explore the feasible dosimetric constraints for pelvic bone marrow (PBM) that can be widely used in rectal cancer patients undergoing chemo-rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“… 11 Also, for rectal cancer, a bone marrow-sparing approach appears to be beneficial and results in lower incidence of acute hematological toxicity. 23 In 2016, Cozzarini et al, already reported leukopenia and thrombocytopenia after postprostatectomy WPRT. 24 Recently, available literature on hematological toxicity after prostate radiotherapy was resumed within a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Also, for rectal cancer, a bone marrow-sparing approach appears to be beneficial and results in lower incidence of acute hematological toxicity. 23 In 2016, Cozzarini et al, already reported leukopenia and thrombocytopenia after postprostatectomy WPRT. 24 Recently, available literature on hematological toxicity after prostate radiotherapy was resumed within a systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol aligns with practices in other institutions. However, BV still exhibits significant variability during RT due to factors such as diet, water intake, and patient age [ 8 ]. To evaluate these differences, we analyzed the discrepancies in BV measured by PBSV3.2 and CT based on gender, treatment objectives (PR and RR), and age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Bladder volume (BV) is a significant factor in determining the target volume for cervical/cervical cancer [ 3 , 4 ], prostate cancer [ 5 , 6 ], and rectal cancer [ 7 , 8 ]. Variations in BV among treatment fractions have been observed; Ahmad et al [ 4 ] found an average reduction of 71% in bladder capacity among patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A future priority in treatment planning may be bone-marrow sparing, as data in primary rectal cancer show that CRT can cause hematological toxicity, leading to dose reductions or treatment interruptions that are associated with worse oncological outcomes. [36,37] However, these findings have not yet translated to clinical practice in the form of constraints.…”
Section: Discussionmentioning
confidence: 99%